2012
DOI: 10.1021/ja304513t
|View full text |Cite
|
Sign up to set email alerts
|

Catalysis in a Porous Molecular Capsule: Activation by Regulated Access to Sixty Metal Centers Spanning a Truncated Icosahedron

Abstract: The 30 cationic {Mo(V)2O4(acetate)}(+) units linking 12 negatively charged pentagonal "ligands," {(Mo(VI))Mo(VI)5O21(H2O)6}(6-) of the porous metal-oxide capsule, [{Mo(VI)6O21(H2O)6}12{Mo(V)2O4(acetate)}30](42-) provide active sites for catalytic transformations of organic "guests". This is demonstrated using a well-behaved model reaction, the fully reversible cleavage and formation of methyl tert-butyl ether (MTBE) under mild conditions in water. Five independent lines of evidence demonstrate that reactions o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
63
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 81 publications
(64 citation statements)
references
References 19 publications
0
63
0
Order By: Relevance
“…showed that regioselective Huisgen reaction is able to take place inside the Keplerate anions,25 while Weinstock et al. reported that the porous capsule provides internal active sites for catalytic transformations 26…”
Section: Introductionmentioning
confidence: 99%
“…showed that regioselective Huisgen reaction is able to take place inside the Keplerate anions,25 while Weinstock et al. reported that the porous capsule provides internal active sites for catalytic transformations 26…”
Section: Introductionmentioning
confidence: 99%
“…This particular finding, related to commensurability between the tridimensional water network and the container, is the major outcome of this study. Such a dual behavior of confined water may have potential applications related to selectivity of ions 47 and specific catalysis, 48 51. In both capsules 100 water molecules were trapped inside the cavity together with 72 coordinated water molecules covering the inner side.…”
Section: Introductionmentioning
confidence: 99%
“…26 , respectively ( Figure S4), that most probably include the 15 remaining fluoride ions (see formula of 3 above) besides water molecules.Though the distinction between fluorine and oxygen is problematical in the present case,itshould be noted that af luoride ion can play the topological role of aw ater molecule as shown for example by the comparison of cyclic [F(H 2 O)] 4 4À [15] and (H 2 O) 8 [23] assemblies.T he largest shell is attracted towards the spherical ligand wall as shown by the corresponding hydrogen-bonding distances;f or details,s ee Figure S4. 26 , respectively ( Figure S4), that most probably include the 15 remaining fluoride ions (see formula of 3 above) besides water molecules.Though the distinction between fluorine and oxygen is problematical in the present case,itshould be noted that af luoride ion can play the topological role of aw ater molecule as shown for example by the comparison of cyclic [F(H 2 O)] 4 4À [15] and (H 2 O) 8 [23] assemblies.T he largest shell is attracted towards the spherical ligand wall as shown by the corresponding hydrogen-bonding distances;f or details,s ee Figure S4.…”
Section: Methodsmentioning
confidence: 99%
“…[26] We are currently exploring the reactivity of the fluoride balls 3a and 4a to further assess the potential of Keplerates as nanoreactors.Apreliminary result refers to hydrolysis of methyl acetate;the related complete results will be reported as soon as possible. [26] We are currently exploring the reactivity of the fluoride balls 3a and 4a to further assess the potential of Keplerates as nanoreactors.Apreliminary result refers to hydrolysis of methyl acetate;the related complete results will be reported as soon as possible.…”
Section: Methodsmentioning
confidence: 99%